Subcellular Localization of Adenosine Diphosphatase in Cultured Pig Arterial Endothelial Cells - Lieberman, Elisabeth G; Leake, David S; Peters, Timothy J (Thrombosis and Haemostasis, 1982)
A role for vessel wall adenosine diphosphatase (ADPase) in limiting platelet aggregation has been suggested by a number of studies. The purpose of this study was to determine the properties and subcellular localization of ADPase in endothelial cells.Homogenates were prepared from subcultured pig aortic endothelial cells and used to determine the kinetics of ADPase activity with a recently described rapid assay employing [²-32P]ADP. The activity was linear with incubation time and homogenate concentration. The pH optimum was 7.4 and the apparent Km was 43 ¼M. The enzyme displayed an absolute divalent cation requirement and its activity was unaffected by levamisole, a specific alkaline phosphatase inhibitor, or by 2-glycerophosphate, a substrate for non-specific phosphatases.Post-nuclear supernatants were prepared from cell homogenates and were fractionated by sucrose density centrifugation. The distribution of ADPase activity in the gradient corresponded to 5'nucleotidase, a plasma membrane marker enzyme, and was clearly distinct from the other organelle marker enzymes. When the cells were treated with the cholesterol-binding agent, digitonin, before being homogenized, the activities of both 5'nucleotidase and ADPase shifted to a denser zone in the gradient, confirming their coincident localization to the plasma membrane.Intact and sonicated cells were incubated with the poorly permeant enzyme inhibitor, diazotized sulphanilic add. With intact cells, ADPase and 5'nucleotidase were inhibited whereas lactate dehydrogenase, an intracellular enzyme, was unaffected; with sonicated cells all three enzymes were inactivated. ADPase is thus an ecto-enzyme on the plasma membrane of cultured pig aortic endothelial cells and is therefore ideally located for a role in limiting platelet aggregation.
Keywords: Adenosine diphosphate; Adenosine diphosphatase; Endothelial cells; Platelet aggregation; Subcellular fractionation